Composite gas sensitive material, gas sensor as well as preparation method and application of composite gas sensitive material

Through gold-modified rhenium disulfide material, the catalytic performance and carrier transmission are improved by using Au-S bonds and Schottky barriers, which solves the poor selectivity and low sensitivity of transition metal disulfide gas-sensitive sensors to ammonia at room temperature. The problem of this problem achieves high sensitivity and fast response ammonia detection.

CN119310140APending Publication Date: 2025-01-14SOUTHERN POWER GRID DIGITAL GRID RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411477104.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing transition metal disulfide gas-sensitive sensors have poor selectivity and low sensitivity to ammonia at room temperature, which limits their use in practical applications.

Method used

Using gold-modified rhenium disulfide material, through Au-S bonding and the formation of Schottky barrier, improves the catalytic performance and carrier transport of the material, reduces the reaction activation energy, promotes the adsorption and reaction of gas molecules, and achieves rapid electrical parameters change.

Benefits of technology

It achieves high sensitivity response and excellent selectivity to ammonia, has fast response speed and high selectivity, and is suitable for the detection of low concentration ammonia.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119310140A_ABST
    Figure CN119310140A_ABST
Patent Text Reader

Abstract

The invention relates to a composite gas-sensitive material, a gas sensor and a preparation method and application of the composite gas-sensitive material. The composite gas sensitive material comprises gold modified rhenium disulfide, and the molar ratio of gold to rhenium disulfide is (0.01-0.15): 1. Wherein the gold has excellent catalytic performance and can reduce the activation energy of the reaction and promote the proceeding of the surface chemical reaction. When the gold is combined with rhenium disulfide, the gold can be used as a catalyst to accelerate the adsorption and reaction process of gas molecules on the surface of the material. Meanwhile, gold and rhenium disulfide form a Schottky barrier, and carrier transmission in the rhenium disulfide material can be adjusted due to the existence of the barrier, so that the electrical property of the material is influenced. When gas molecules are adsorbed, the change of the Schottky barrier can cause the rapid change of parameters such as resistance or capacitance of the material, so that rapid response is realized, and the material has important significance in improving the sensing performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of gas sensors, and in particular to a composite gas-sensitive material, a gas sensor, and a preparation method and application thereof. Background Art

[0002] Ammonia is one of the most common chemical gases in human daily life and industrial production. High concentrations of ammonia are harmful to human health and the ecological environment. High-performance ammonia sensors are of great significance for environmental monitoring and human health protection.

[0003] Transition metal disulfides are sensitive materials for chemiresistive gas sensors operating at room temperature due to their inherent high surface-to-volume ratio and strong interaction with gas molecules. However, the current transition metal disulfide gas sensors have the disadvantages of poor selectivity and low sensitivity, which is still an important bottleneck hindering their practical application in room temperature ammonia sensing.

[0004] Therefore, the traditional technology still needs to be improved. Summary of the invention

[0005] Based on this, it is necessary to provide a composite gas-sensitive material, a gas sensor and its preparation method and application with excellent photosensitivity, high sensitivity and selectivity. The specific scheme is as follows:

[0006] In a first aspect of the present application, a composite gas-sensitive material is provided, comprising gold-modified rhenium disulfide, wherein the molar ratio of the gold to the rhenium disulfide is (0.01-0.15):1.

[0007] In some embodiments, the gold forms an Au—S bond with the sulfur element in the rhenium disulfide.

[0008] The above-mentioned composite gas-sensitive material includes rhenium disulfide modified with gold in a specific ratio, wherein gold has excellent catalytic properties, can reduce the activation energy of the reaction, and promote the surface chemical reaction. When combined with rhenium disulfide, gold can act as a catalyst to accelerate the adsorption and reaction process of gas molecules on the surface of the material. At the same time, gold and rhenium disulfide form a Schottky barrier, and the existence of this barrier can regulate the carrier transport in the rhenium disulfide material and affect the electrical properties of the material. When gas molecules are adsorbed, changes in the Schottky barrier can lead to rapid changes in parameters such as material resistance or capacitance, thereby achieving rapid response, which is of great significance for improving the sensing performance of the material.

[0009] The second aspect of the present application provides a method for preparing the composite gas-sensitive material, comprising the following steps:

[0010] dissolving perrhenate, thiourea and hydroxylamine hydrochloride in a first solvent and mixing to obtain a premixed solution;

[0011] The premixed solution is subjected to a hydrothermal reaction, and a precipitate is collected by centrifugation to obtain a rhenium disulfide nanoparticle.

[0012] Annealing the rhenium disulfide nano-coarse to obtain a rhenium disulfide nano-material;

[0013] The rhenium disulfide nanomaterial and the gold source are mixed in a second solvent and dried to obtain the composite gas-sensitive material.

[0014] In some embodiments, the preparation method satisfies at least one of the conditions (1) to (7):

[0015] (1) The first solvent and the second solvent are each independently selected from at least one of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone;

[0016] (2) The concentration of the perrhenate is 0.02M to 0.05M;

[0017] (3) The concentration of thiourea is 0.02M~0.25M;

[0018] (4) The concentration of hydroxylamine hydrochloride is 0.04M~0.10M;

[0019] (5) The gold source comprises gold chloride hydrate;

[0020] (6) The temperature of the hydrothermal reaction is 150°C to 240°C;

[0021] (7) The hydrothermal reaction time is 12 h to 24 h.

[0022] In some embodiments, the annealing treatment comprises the following steps: in a protective gas, heating the rhenium disulfide nanoparticles to 400° C. to 600° C. at a heating rate of 5° C. to 10° C. per minute, and keeping the temperature for 0.5 h to 2 h.

[0023] In some of the embodiments, a gas-sensitive layer is included, and the gas-sensitive layer includes the above-mentioned composite gas-sensitive material or a composite gas-sensitive material prepared by the above-mentioned method for preparing the composite gas-sensitive material.

[0024] In some embodiments, the gas sensor further includes a substrate and interdigital electrodes, wherein the interdigital electrodes are disposed on at least one side of the substrate, and the gas sensitive layer is disposed on a surface of the interdigital electrodes away from the substrate.

[0025] In some embodiments, the substrate is selected from at least one of a silicon substrate, a polymer substrate, a ceramic substrate and a sapphire substrate;

[0026] And / or, the distance between the positive and negative electrodes of the interdigitated electrodes is 200 μm to 800 μm;

[0027] And / or, the number of the interdigital electrodes is one or more. When the number of the interdigital electrodes is plural, the interval between two adjacent interdigital electrodes is 50 μm to 400 μm.

[0028] In a third aspect of the present application, a method for preparing a gas sensor is provided, comprising the following steps:

[0029] disposing interdigital electrodes on a substrate;

[0030] The composite gas-sensitive material or the composite gas-sensitive material prepared by the composite gas-sensitive material preparation method is made into a gas-sensitive layer dispersion, and the gas-sensitive layer dispersion is coated on the surface of the interdigitated electrode away from the substrate, and a gas-sensitive layer is formed after drying.

[0031] In a fourth aspect of the present application, a gas detection device is provided, comprising the above-mentioned gas sensor or a gas sensor prepared by the above-mentioned method for preparing the gas sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A schematic diagram of the principle of the gas sensitive layer responding to ammonia in the gas sensor structure prepared in one embodiment of the present application;

[0033] FIG2 is a transmission electron microscope image of the composite gas-sensitive material in Example 3;

[0034] Figure 3 is the XRD pattern of the composite gas-sensitive material in Example 3;

[0035] Figure 4 It is a repeated curve diagram of the sensor of the composite gas-sensitive material in Example 3 in the absence of ultraviolet rays and in the presence of ultraviolet rays;

[0036] Figure 5 This is a test graph of the sensor's response to 0.5-500 ppm ammonia when the molar content of gold nanoparticles is 5% under ultraviolet light in Example 3;

[0037] Figure 6 This is a test graph of the response of the sensors corresponding to the gas-sensitive materials in Examples 1 to 5 and Comparative Examples 1 to 2 to 50 ppm ammonia gas. DETAILED DESCRIPTION

[0038] For ease of understanding of the present application, the present application will be described more fully below, and preferred embodiments of the present application are provided. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0040] The term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprising one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. The indefinite articles "a kind of" and "one" before the elements or components of the present application are not restrictive to the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "one" or "a kind of" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number obviously refers only to the singular form. The meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0041] The weight of the relevant components mentioned in the specification of the examples of this application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the specification of the examples of this application, it is within the scope disclosed in the specification of the examples of this application. Specifically, the weight described in the specification of the examples of this application can be mass units known in the chemical industry such as μg, mg, g, and kg.

[0042] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.

[0043] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0044] One embodiment of the present application provides a composite gas-sensitive material, including gold-modified rhenium disulfide, wherein the molar ratio of the gold to the rhenium disulfide is (0.01-0.15):1.

[0045] The molar ratio of the above gold to the above rhenium disulfide is in the range of "(0.01-0.15):1", that is, the minimum and maximum values ​​of the range of (0.01-0.15):1, and every value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, 0.06:1, 0.0.7:1, 0.08:1, 0.09:1, 0.1:1, 0.11:1, 0.12:1, 0.13:1, 0.14:1 or 0.15:1; or a range consisting of any two of these values, including, as an example, 0.02:1-0.1:1.

[0046] The above-mentioned composite gas-sensitive material includes rhenium disulfide modified with gold in a specific ratio, wherein gold has excellent catalytic properties, can reduce the activation energy of the reaction, and promote the surface chemical reaction. When combined with rhenium disulfide, gold can act as a catalyst to accelerate the adsorption and reaction process of gas molecules on the surface of the material. At the same time, gold and rhenium disulfide form a Schottky barrier, and the existence of this barrier can regulate the carrier transport in the rhenium disulfide material and affect the electrical properties of the material. When gas molecules are adsorbed, changes in the Schottky barrier can lead to rapid changes in parameters such as material resistance or capacitance, thereby achieving rapid response, which is of great significance for improving the sensing performance of the material.

[0047] In some embodiments, the gold forms an Au—S bond with the sulfur element in the rhenium disulfide.

[0048] It can be understood that the above-mentioned gold and rhenium disulfide form Au-S bonds through chemical adsorption and in-situ reduction. The Au-S bond is a relatively strong chemical bond with high binding energy, which makes it have high stability in the composite gas-sensitive material system. This strong binding force enables the compound containing the Au-S bond to maintain a relatively stable structure under certain conditions and is not easily destroyed, thereby improving the selectivity and stability of the composite gas-sensitive material.

[0049] Another embodiment of the present application provides a method for preparing the above-mentioned composite gas-sensitive material, including steps S10 to S40.

[0050] Step S10: dissolving perrhenate, thiourea and hydroxylamine hydrochloride in a first solvent and mixing them to obtain a premixed solution.

[0051] In some embodiments, the concentration of the perrhenate is 0.02M-0.05M.

[0052] Specifically, the above-mentioned perrhenate includes ammonium perrhenate.

[0053] In some embodiments, the concentration of thiourea is 0.02M~0.25M.

[0054] In some embodiments, the concentration of the hydroxylamine hydrochloride is 0.04M~0.10M.

[0055] Step S20: subjecting the premixed solution to a hydrothermal reaction, and centrifuging to obtain a precipitate to obtain a rhenium disulfide nanoparticle.

[0056] In some embodiments, the temperature of the hydrothermal reaction is 150°C to 240°C.

[0057] The temperature of the hydrothermal reaction can range from 150°C to 240°C, that is, the minimum and maximum values ​​of the range of 150°C to 240°C, and every value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C or 250°C; or a range consisting of any two of these values, including, for example, 150°C to 200°C.

[0058] It can be understood that controlling the temperature of the above hydrothermal reaction within the above specific range can effectively adjust key properties such as the reaction rate and the crystal structure or size of the product, thereby optimizing the performance of the reaction product.

[0059] In some embodiments, the hydrothermal reaction time is 12 h to 24 h.

[0060] The time range of the hydrothermal reaction is "12h~24h", that is, the minimum and maximum values ​​of the range of 12h~24h, and each value between the minimum and maximum values. Specific examples include, but are not limited to, the point values ​​in the embodiments and the following point values: 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h, 18.5h, 19h, 19.5h, 20h, 20.5h, 21h, 21.5h, 22h, 22.5h, 23h, 23.5h or 24h; or a range composed of any two of these values, as an example, including: 12h~18h.

[0061] It can be understood that controlling the time of the above-mentioned hydrothermal reaction within the above-mentioned specific range can effectively regulate the crystallinity and structural properties of the product of the reaction process.

[0062] In some embodiments, the centrifugal washing process is performed at a centrifugal speed of 5000 rpm to 8000 rpm, and the time for the centrifugal washing process is 5 min to 30 min.

[0063] In some embodiments, the mixing method is magnetic stirring or mechanical stirring.

[0064] In some embodiments, the stirring speed is 100 rpm to 1500 rpm, and the stirring time is 5 min to 30 min.

[0065] Step S30: annealing the above-mentioned rhenium disulfide nano-bricks to obtain rhenium disulfide nano-materials.

[0066] In some embodiments, the annealing treatment comprises the following steps: in a protective gas, heating the rhenium disulfide nanoparticles to 400° C. to 600° C. at a heating rate of 5° C. to 10° C. per minute, and keeping the temperature for 0.5 h to 2 h.

[0067] It can be understood that controlling the conditions of the above annealing treatment within the above specific range can effectively improve the crystal quality of the material, eliminate defects, and improve its stability and conductivity. Reasonable heating rate and holding time can avoid excessive oxidation or sintering of the material surface, while promoting the uniform growth of rhenium disulfide nanomaterials and enhancing their optical, electrical or gas-sensitive properties.

[0068] Step S40: Mix the above-mentioned rhenium disulfide nanomaterial and the gold source in a second solvent, and dry them to obtain the above-mentioned composite gas-sensitive material.

[0069] In some of these embodiments, the upper gold source includes gold chloride hydrate.

[0070] In some embodiments, the particle size of the rhenium disulfide nanomaterial is 20 nm to 50 nm.

[0071] In some embodiments, the gold nanoparticles have a particle size of 5 nm to 10 nm.

[0072] In some embodiments, the first solvent and the second solvent are independently selected from at least one of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone.

[0073] In the preparation method of a composite gas-sensitive material provided in the present application, ammonium perrhenate, hydroxylamine hydrochloride, and thiourea are used as raw materials, and then a hydrothermal method is used to prepare rhenium disulfide nanosheets. This method has simple steps and a simple process, does not require complex reaction control conditions, has a low reaction temperature, and is easy to mass-produce high-quality rhenium disulfide nanosheets.

[0074] Another embodiment of the present application further provides a gas sensor, including a gas-sensitive layer, wherein the gas-sensitive layer includes the composite gas-sensitive material or a gas-sensitive material prepared by the method for preparing the composite gas-sensitive material.

[0075] In some embodiments, the gas sensor further comprises a substrate and interdigital electrodes, wherein the interdigital electrodes are disposed on at least one side of the substrate, and the gas sensitive layer is disposed on a surface of the interdigital electrodes away from the substrate.

[0076] In some embodiments, the substrate is selected from at least one of a silicon substrate, a polymer substrate, a ceramic substrate and a sapphire substrate.

[0077] In some embodiments, the distance between the positive and negative electrodes of the interdigitated electrodes is 200 μm to 800 μm.

[0078] In some embodiments, the number of the interdigital electrodes is one or more. When the number of the interdigital electrodes is plural, the interval between two adjacent interdigital electrodes is 50 μm-400 μm.

[0079] In some embodiments, the thickness of the gas sensitive layer is 3 μm to 8 μm.

[0080] The gas sensor of the present application can achieve a highly sensitive response to ammonia gas, has a fast response speed, and has excellent photosensitivity, higher sensitivity and selectivity.

[0081] An embodiment of the present application provides a method for preparing the above-mentioned gas sensor, comprising steps a to b.

[0082] Step a: Arrange interdigital electrodes on a substrate.

[0083] Step b: prepare a gas-sensitive layer dispersion by making the composite gas-sensitive material or the composite gas-sensitive material prepared by the preparation method of the composite gas-sensitive material, apply the gas-sensitive layer dispersion onto the surface of the interdigitated electrode away from the substrate, form a gas-sensitive layer after drying, and prepare the gas sensor.

[0084] Specifically, in step b, the gold-modified rhenium disulfide nanomaterial is added to the third solvent at a concentration of 1 mg / L to 10 mg / L, and ultrasonically treated at 50 kHz to 100 kHz for 2 min to 20 min to uniformly disperse the gold-modified rhenium disulfide nanomaterial in the third solvent, thereby obtaining the dispersion.

[0085] In some embodiments, the third solvent is selected from at least one of deionized water, N,N-dimethylformamide, N,N-dimethylacetamide, methanol, ethanol and acetone.

[0086] The preparation method of the gas sensor adopts micromachining method to prepare interdigital electrodes on a substrate, and then covers the surface with a layer of nanocomposite material as a gas sensitive layer to obtain a gas sensor. The method is simple, has high preparation accuracy, and the obtained gas sensor has stable quality.

[0087] One embodiment of the present application further provides a gas detection device, including the above-mentioned gas sensor or a gas sensor prepared by the above-mentioned method for preparing the gas sensor.

[0088] The above gas detection device can achieve a high sensitivity response to ammonia gas, and has excellent photosensitivity, higher sensitivity and selectivity. Low concentration ammonia can be detected under the activation of ultraviolet light. The above sensor has an ultraviolet wavelength of 365 nm and a fixed light intensity of 3 mW / cm -2 Under these conditions, the response value to 50 ppm ammonia at room temperature can reach 1.15, and the theoretical detection limit is as low as 12 ppb.

[0089] Figure 1 A schematic diagram of the principle of the gas sensing layer responding to ammonia in a gas sensor structure prepared in one embodiment of the present application. An efficient gas sensing process is achieved by combining physical / chemical adsorption and charge transfer, and the sensing process has high specificity, high sensitivity and fast response speed.

[0090] The present application will be described below in conjunction with specific embodiments, but the present application is not limited to the following embodiments. It should be understood that the attached claims summarize the scope of the present application. Under the guidance of the concept of the present application, technical personnel in the field should realize that certain changes made to the various embodiments of the present application will be covered by the spirit and scope of the claims of the present application.

[0091] In order to make the purpose, technical solutions and advantages of the present application more concise and clear, the present application is described with the following specific embodiments, but the present application is by no means limited to these embodiments. The embodiments described below are only preferred embodiments of the present application and can be used to describe the present application, and cannot be understood as limiting the scope of the present application. It should be pointed out that any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

[0092] Example 1

[0093] (1) Dissolve 1 mmol of ammonium perrhenate, 2 mmol of thiourea and 2 mmol of hydroxylamine hydrochloride in 30 mL of deionized water and stir to obtain a premix.

[0094] (2) The obtained premixed solution was heated at 200°C for 20 hours. The premixed solution was ultrasonically treated at a power of 400 W for 30 minutes. The dispersion after ultrasonic treatment was centrifuged at 5000 rpm for 30 minutes to obtain a supernatant, which was a rhenium disulfide nanosheet solution. The supernatant was then centrifuged at 8000 rpm for 30 minutes to obtain rhenium disulfide nanoparticles.

[0095] (3) The collected rhenium disulfide nano-coarse powder was annealed at 500° C. for 30 minutes in a nitrogen environment to obtain rhenium disulfide nanosheets.

[0096] (4) Disperse 10 mg of the prepared rhenium disulfide nanomaterial into 5 mL of 70 vol% ethanol aqueous solution. Use an ultrasonic crusher at a power of 400 W for 30 minutes to obtain a rhenium disulfide dispersion.

[0097] (5) Dissolve gold chloride trihydrate in deionized water and use an ultrasonic disruptor at a power of 400 W for 20 minutes to obtain a gold chloride dispersion.

[0098] (6) 400 μL of 1 mM gold chloride dispersion was slowly dripped into the rhenium disulfide dispersion under magnetic stirring at a speed of 1500 rpm, and stirred for 30 minutes. The mixed solution was ultrasonically treated for 4 hours to obtain a composite material with a gold molar content of 1% of the rhenium disulfide nanosheets. The final product was washed by centrifugation with water and ethanol several times, and then vacuum dried at 60°C for 12 hours to obtain the gold-modified rhenium disulfide nanomaterial.

[0099] (7) The gold-modified rhenium disulfide nanomaterial was added to deionized water at a concentration of 1 mg / L and ultrasonicated at 40 kHz for 10 minutes to uniformly disperse the composite material in the deionized water, thereby obtaining a dispersion of the gold-modified rhenium disulfide nanomaterial. The gold electrode was prepared by micromachining technology, and the spacing between the positive and negative electrodes was controlled to be 800 μm, and the spacing between adjacent electrodes was 300 μm. 1 μL of the dispersion of the gold-modified rhenium disulfide nanomaterial was added dropwise to the electrode surface and vacuum dried at 60°C for 1 hour to obtain a room temperature low-concentration ammonia sensor of gold-modified rhenium disulfide nanomaterial.

[0100] Example 2

[0101] (1) Dissolve 1 mmol of ammonium perrhenate, 2 mmol of thiourea and 2 mmol of hydroxylamine hydrochloride in 30 mL of deionized water and stir to obtain a premix.

[0102] (2) The obtained premixed solution was heated at 200°C for 20 hours. The premixed solution was ultrasonically treated at a power of 400 W for 30 minutes. The dispersion after ultrasonic treatment was centrifuged at 5000 rpm for 30 minutes to obtain a supernatant, which was a rhenium disulfide nanosheet solution. The supernatant was then centrifuged at 8000 rpm for 30 minutes to obtain rhenium disulfide nanoparticles.

[0103] (3) The collected rhenium disulfide nano-coarse powder was annealed at 500° C. for 30 minutes in a nitrogen environment to obtain rhenium disulfide nanosheets.

[0104] (4) Disperse 10 mg of the prepared rhenium disulfide nanomaterial into 5 mL of 70 vol% ethanol aqueous solution. Use an ultrasonic crusher at a power of 400 W for 30 minutes to obtain a rhenium disulfide dispersion.

[0105] (5) Dissolve gold chloride trihydrate in deionized water and use an ultrasonic disruptor at a power of 400 W for 20 minutes to obtain a gold chloride dispersion.

[0106] (6) 800 μL of 1 mM gold chloride dispersion was slowly dripped into the rhenium disulfide dispersion under magnetic stirring at a speed of 1500 rpm, and stirred for 30 minutes. The mixed solution was ultrasonically treated for 4 hours to obtain a composite material with a gold molar content of 2% of the rhenium disulfide nanosheets. The final product was washed by centrifugation with water and ethanol several times, and then vacuum dried at 60°C for 12 hours to obtain gold-modified rhenium disulfide nanomaterials.

[0107] (7) The gold-modified rhenium disulfide nanomaterial was added to deionized water at a concentration of 1 mg / L and ultrasonicated at 40 kHz for 10 minutes to uniformly disperse the composite material in the deionized water, thereby obtaining a dispersion of the gold-modified rhenium disulfide nanomaterial. The gold electrode was prepared by micromachining technology, and the spacing between the positive and negative electrodes was controlled to be 800 μm, and the spacing between adjacent electrodes was 300 μm. 1 μL of the dispersion of the gold-modified rhenium disulfide nanomaterial was added dropwise to the electrode surface and vacuum dried at 60°C for 1 hour to obtain a room temperature low-concentration ammonia sensor of gold-modified rhenium disulfide nanomaterial.

[0108] Example 3

[0109] (1) Dissolve 1 mmol of ammonium perrhenate, 2 mmol of thiourea and 2 mmol of hydroxylamine hydrochloride in 30 mL of deionized water and stir to obtain a premix.

[0110] (2) The obtained premixed solution was heated at 200°C for 20 hours. The premixed solution was ultrasonically treated at a power of 400 W for 30 minutes. The dispersion after ultrasonic treatment was centrifuged at 5000 rpm for 30 minutes to obtain a supernatant, which was a rhenium disulfide nanosheet solution. The supernatant was then centrifuged at 8000 rpm for 30 minutes to obtain rhenium disulfide nanoparticles.

[0111] (3) The collected rhenium disulfide nano-coarse powder was annealed at 500° C. for 30 minutes in a nitrogen environment to obtain rhenium disulfide nanosheets.

[0112] (4) Disperse 10 mg of the prepared rhenium disulfide nanomaterial into 5 mL of 70 vol% ethanol aqueous solution. Use an ultrasonic crusher at a power of 400 W for 30 minutes to obtain a rhenium disulfide dispersion.

[0113] (5) Dissolve gold chloride trihydrate in deionized water and use an ultrasonic disruptor at a power of 400 W for 20 minutes to obtain a gold chloride dispersion.

[0114] (6) 2 mL of 1 mM gold chloride dispersion was slowly dripped into the rhenium disulfide dispersion under magnetic stirring at a speed of 1500 rpm and stirred for 30 minutes. The mixed solution was ultrasonically treated for 4 hours to obtain a composite material with a gold molar content of 5% of the rhenium disulfide nanosheets. The final product was washed by centrifugation with water and ethanol several times and then vacuum dried at 60°C for 12 hours to obtain the gold-modified rhenium disulfide nanomaterial.

[0115] (7) The gold-modified rhenium disulfide nanomaterial was added to deionized water at a concentration of 1 mg / L and ultrasonicated at 40 kHz for 10 minutes to uniformly disperse the composite material in the deionized water, thereby obtaining a dispersion of the gold-modified rhenium disulfide nanomaterial. The gold electrode was prepared by micromachining technology, and the spacing between the positive and negative electrodes was controlled to be 800 μm, and the spacing between adjacent electrodes was 300 μm. 1 μL of the dispersion of the gold-modified rhenium disulfide nanomaterial was added dropwise to the electrode surface and vacuum dried at 60°C for 1 hour to obtain a room temperature low-concentration ammonia sensor of gold-modified rhenium disulfide nanomaterial.

[0116] Example 4

[0117] (1) Dissolve 1 mmol of ammonium perrhenate, 2 mmol of thiourea and 2 mmol of hydroxylamine hydrochloride in 30 mL of deionized water and stir to obtain a premix.

[0118] (2) The obtained premixed solution was heated at 200°C for 20 hours. The premixed solution was ultrasonically treated at a power of 400 W for 30 minutes. The dispersion after ultrasonic treatment was centrifuged at 5000 rpm for 30 minutes to obtain a supernatant, which was a rhenium disulfide nanosheet solution. The supernatant was then centrifuged at 8000 rpm for 30 minutes to obtain rhenium disulfide nanoparticles.

[0119] (3) The collected rhenium disulfide nano-coarse powder was annealed at 500° C. for 30 minutes in a nitrogen environment to obtain rhenium disulfide nanosheets.

[0120] (4) Disperse 10 mg of the prepared rhenium disulfide nanomaterial into 5 mL of 70 vol% ethanol aqueous solution. Use an ultrasonic crusher at a power of 400 W for 30 minutes to obtain a rhenium disulfide dispersion.

[0121] (5) Dissolve gold chloride trihydrate in deionized water and use an ultrasonic disruptor at a power of 400 W for 20 minutes to obtain a gold chloride dispersion.

[0122] (6) 4 mL of 1 mM gold chloride dispersion was slowly dripped into the rhenium disulfide dispersion under magnetic stirring at a speed of 1500 rpm and stirred for 30 minutes. The mixed solution was ultrasonically treated for 4 hours to obtain a composite material with a gold molar content of 10% of the rhenium disulfide nanosheets. The final product was washed by centrifugation with water and ethanol several times and then vacuum dried at 60°C for 12 hours to obtain the gold-modified rhenium disulfide nanomaterial.

[0123] (7) The gold-modified rhenium disulfide nanomaterial was added to deionized water at a concentration of 1 mg / L and ultrasonicated at 40 kHz for 10 minutes to uniformly disperse the composite material in the deionized water, thereby obtaining a dispersion of the gold-modified rhenium disulfide nanomaterial. The gold electrode was prepared by micromachining technology, and the spacing between the positive and negative electrodes was controlled to be 800 μm, and the spacing between adjacent electrodes was 300 μm. 1 μL of the dispersion of the gold-modified rhenium disulfide nanomaterial was added dropwise to the electrode surface and vacuum dried at 60°C for 1 hour to obtain a room temperature low-concentration ammonia sensor of gold-modified rhenium disulfide nanomaterial.

[0124] Example 5

[0125] (1) Dissolve 1 mmol of ammonium perrhenate, 2 mmol of thiourea and 2 mmol of hydroxylamine hydrochloride in 30 mL of deionized water and stir to obtain a premix.

[0126] (2) The obtained premixed solution was heated at 200°C for 20 hours. The premixed solution was ultrasonically treated at a power of 400 W for 30 minutes. The dispersion after ultrasonic treatment was centrifuged at 5000 rpm for 30 minutes to obtain a supernatant, which was a rhenium disulfide nanosheet solution. The supernatant was then centrifuged at 8000 rpm for 30 minutes to obtain rhenium disulfide nanoparticles.

[0127] (3) The collected rhenium disulfide nano-coarse powder was annealed at 500° C. for 30 minutes in a nitrogen environment to obtain rhenium disulfide nanosheets.

[0128] (4) Disperse 10 mg of the prepared rhenium disulfide nanomaterial into 5 mL of 70 vol% ethanol aqueous solution. Use an ultrasonic crusher at a power of 400 W for 30 minutes to obtain a rhenium disulfide dispersion.

[0129] (5) Dissolve gold chloride trihydrate in deionized water and use an ultrasonic disruptor at a power of 400 W for 20 minutes to obtain a gold chloride dispersion.

[0130] (6) 6 mL of 1 mM gold chloride dispersion was slowly dripped into the rhenium disulfide dispersion under magnetic stirring at a speed of 1500 rpm and stirred for 30 minutes. The mixed solution was ultrasonically treated for 4 hours to obtain a composite material with a gold molar content of 15% of the rhenium disulfide nanosheets. The final product was washed by centrifugation with water and ethanol several times and then vacuum dried at 60°C for 12 hours to obtain the gold-modified rhenium disulfide nanomaterial.

[0131] (7) The gold-modified rhenium disulfide nanomaterial was added to deionized water at a concentration of 1 mg / L and ultrasonicated at 40 kHz for 10 minutes to uniformly disperse the composite material in the deionized water, thereby obtaining a dispersion of the gold-modified rhenium disulfide nanomaterial. The gold electrode was prepared by micromachining technology, and the spacing between the positive and negative electrodes was controlled to be 800 μm, and the spacing between adjacent electrodes was 300 μm. 1 μL of the dispersion of the gold-modified rhenium disulfide nanomaterial was added dropwise to the electrode surface and vacuum dried at 60°C for 1 hour to obtain a room temperature low-concentration ammonia sensor of gold-modified rhenium disulfide nanomaterial.

[0132] Comparative Example 1

[0133] (1) Dissolve 1 mmol of ammonium perrhenate, 2 mmol of thiourea and 2 mmol of hydroxylamine hydrochloride in 30 mL of deionized water and stir to obtain a premix.

[0134] (2) The obtained premixed solution was heated at 200°C for 20 hours. The premixed solution was ultrasonically treated at a power of 400 W for 30 minutes. The dispersion after ultrasonic treatment was centrifuged at 5000 rpm for 30 minutes to obtain a supernatant, which was a rhenium disulfide nanosheet solution. The supernatant was then centrifuged at 8000 rpm for 30 minutes to obtain rhenium disulfide nanoparticles.

[0135] (3) The collected rhenium disulfide nano-coarse powder was annealed at 500°C for 30 minutes in a nitrogen environment to obtain a room temperature low-concentration ammonia sensor made of rhenium disulfide nanomaterials without gold modification.

[0136] Comparative Example 2

[0137] (1) Dissolve 1 mmol of ammonium perrhenate, 2 mmol of thiourea and 2 mmol of hydroxylamine hydrochloride in 30 mL of deionized water and stir to obtain a premix.

[0138] (2) The obtained premixed solution was heated at 200°C for 20 hours. The premixed solution was ultrasonically treated at a power of 400 W for 30 minutes. The dispersion after ultrasonic treatment was centrifuged at 5000 rpm for 30 minutes to obtain a supernatant, which was a rhenium disulfide nanosheet solution. The supernatant was then centrifuged at 8000 rpm for 30 minutes to obtain rhenium disulfide nanoparticles.

[0139] (3) The collected rhenium disulfide nano-coarse powder was annealed at 500° C. for 30 minutes in a nitrogen environment to obtain rhenium disulfide nanosheets.

[0140] (4) Disperse 10 mg of the prepared rhenium disulfide nanomaterial into 5 mL of 70 vol% ethanol aqueous solution. Use an ultrasonic crusher at a power of 400 W for 30 minutes to obtain a rhenium disulfide dispersion.

[0141] (5) Dissolve gold chloride trihydrate in deionized water and use an ultrasonic disruptor at a power of 400 W for 20 minutes to obtain a gold chloride dispersion.

[0142] (6) 8 mL of 1 mM gold chloride dispersion was slowly dripped into the rhenium disulfide dispersion under magnetic stirring at a speed of 1500 rpm and stirred for 30 minutes. The mixed solution was ultrasonically treated for 4 hours to obtain a composite material with a gold molar content of 20% of the rhenium disulfide nanosheets. The final product was washed by centrifugation with water and ethanol several times and then vacuum dried at 60°C for 12 hours to obtain the gold-modified rhenium disulfide nanomaterial.

[0143] (7) The gold-modified rhenium disulfide nanomaterial was added to deionized water at a concentration of 1 mg / L and ultrasonicated at 40 kHz for 10 minutes to uniformly disperse the composite material in the deionized water, thereby obtaining a dispersion of the gold-modified rhenium disulfide nanomaterial. The gold electrode was prepared by micromachining technology, and the spacing between the positive and negative electrodes was controlled to be 800 μm, and the spacing between adjacent electrodes was 300 μm. 1 μL of the dispersion of the gold-modified rhenium disulfide nanomaterial was added dropwise to the electrode surface and vacuum dried at 60°C for 1 hour to obtain a room temperature low-concentration ammonia sensor of gold-modified rhenium disulfide nanomaterial.

[0144] test:

[0145] 1. The gold-modified rhenium disulfide nanomaterials prepared in each embodiment were observed for microstructure using a scanning electron microscope;

[0146] 2. The gold-modified rhenium disulfide nanomaterials prepared in each embodiment were tested for purity and crystallinity using an X-ray diffractometer;

[0147] 3. The performance of the sensor in each embodiment was tested. The gas-sensitive element was aged at room temperature for 24 h until the current curve was stable. Ammonia gas was injected into the test chamber, and the real-time current of the sensor was recorded using a semiconductor parameter analyzer.

[0148] FIG2 is a scanning electron microscope image of the gold-modified rhenium disulfide nanomaterial in Example 3. It can be clearly observed that the prepared gold-modified rhenium disulfide nanomaterial has a nano-like morphology. Figure 3 This is the XRD diagram of the gold-modified rhenium disulfide nanomaterial in Example 3. It can be observed that the prepared gold-modified rhenium disulfide nanomaterial has good crystal phase purity and crystallinity, indicating that the gold-modified rhenium disulfide nanomaterial has been successfully synthesized. Figure 4 When the molar content of gold nanoparticles in Example 3 is 5%, the repeated curves of the sensor under conditions without ultraviolet light and with ultraviolet light indicate that under ultraviolet light irradiation, the response performance of the sensor is enhanced by 4 times, and there is no obvious attenuation of sensing performance after 6 consecutive cycles. Figure 5 The sensor response when the molar content of gold nanoparticles is 5% and the response to 0.5-500 ppm ammonia under ultraviolet light in Example 3 indicate that the sensor has a good sensing response to 0.5-500 ppm ammonia and has good ammonia detection capability. Figure 6 The molar percentage of gold nanoparticles in the gas-sensitive material of the gold-modified rhenium disulfide nanomaterial room temperature low-concentration ammonia sensor in Example 3 relative to the rhenium disulfide base material is 1%, 2%, 5%, 10% and 15%. The response of the sensors to 50 ppm ammonia is compared. From left to right, they are Comparative Example 1, Example 1, Example 2, Example 3, Example 4, Example 5 and the sensors corresponding to the gas-sensitive materials in Comparative Example 2 to 50 ppm ammonia response, indicating that the sensors of each molar content in the examples have a good response to ammonia relative to the comparative examples.

[0149] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0150] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A composite gas-sensitive material, characterized in that: It includes gold-modified rhenium disulfide, wherein the molar ratio of the gold to the rhenium disulfide is (0.01-0.15):

1.

2. The composite gas-sensitive material according to claim 1, characterized in that: The gold forms an Au—S bond with the sulfur element in the rhenium disulfide.

3. The method for preparing the composite gas-sensitive material according to claim 1, characterized in that: The following steps are involved: dissolving perrhenate, thiourea and hydroxylamine hydrochloride in a first solvent and mixing to obtain a premixed solution; The premixed solution is subjected to a hydrothermal reaction, and a precipitate is collected by centrifugation to obtain a rhenium disulfide nanoparticle. Annealing the rhenium disulfide nano-coarse to obtain a rhenium disulfide nano-material; The rhenium disulfide nanomaterial and the gold source are mixed in a second solvent and dried to obtain the composite gas-sensitive material.

4. The method for preparing the composite gas-sensitive material according to claim 3, characterized in that: The preparation method satisfies at least one of the conditions (1) to (7): (1) The first solvent and the second solvent are each independently selected from at least one of deionized water, N,N-dimethylformamide, methanol, ethanol and acetone; (2) The concentration of the perrhenate is 0.02M to 0.05M; (3) The concentration of thiourea is 0.02M~0.25M; (4) The concentration of hydroxylamine hydrochloride is 0.04M~0.10M; (5) The gold source comprises gold chloride hydrate; (6) The temperature of the hydrothermal reaction is 150°C to 240°C; (7) The hydrothermal reaction time is 12 h to 24 h.

5. The method for preparing a composite gas-sensitive material according to any one of claims 3 to 4, characterized in that: The annealing treatment comprises the following steps: in a protective gas, heating the rhenium disulfide nano-coarse body to 400° C. to 600° C. at a heating rate of 5° C. to 10° C. per minute, and keeping the temperature for 0.5 h to 2 h.

6. A gas sensor, characterized in that: The invention comprises a gas-sensitive layer, wherein the gas-sensitive layer comprises the composite gas-sensitive material according to any one of claims 1 to 2 or a composite gas-sensitive material prepared by the method for preparing the composite gas-sensitive material according to any one of claims 3 to 5.

7. The gas sensor according to claim 6, characterized in that The gas sensor further comprises a substrate and interdigital electrodes, wherein the interdigital electrodes are arranged on at least one side of the substrate, and the gas sensitive layer is arranged on a surface of the interdigital electrodes which is away from the substrate.

8. The gas sensor according to claim 7, characterized in that The substrate is selected from at least one of a silicon substrate, a polymer substrate, a ceramic substrate and a sapphire substrate; And / or, the distance between the positive and negative electrodes of the interdigitated electrodes is 200 μm to 800 μm; And / or, the number of the interdigital electrodes is one or more. When the number of the interdigital electrodes is plural, the interval between two adjacent interdigital electrodes is 50 μm to 400 μm.

9. A method for preparing a gas sensor, characterized in that: The following steps are involved: disposing interdigital electrodes on a substrate; The composite gas-sensitive material according to any one of claims 1 to 2 or the composite gas-sensitive material prepared by the preparation method of the composite gas-sensitive material according to any one of claims 3 to 5 is made into a gas-sensitive layer dispersion, and the gas-sensitive layer dispersion is coated on the surface of the side of the interdigital electrode away from the substrate, and a gas-sensitive layer is formed after drying.

10. A gas detection device, characterized in that: A gas sensor comprising the gas sensor according to any one of claims 6 to 8 or a gas sensor prepared by the method for preparing the gas sensor according to claim 9.

Citation Information

Cited By

  • Mellitene-based molecularly confined ternary gas sensing material and preparation method thereof

    CN122671495A